Streptococcus pneumoniae: A Cause of Primary Lung Abscess in a Child - Kelly S MacDonald; Volia M de Carvalho; Lawrence Liebert; Joanne E Embree (Canadian Journal of Infectious Diseases)
A case of primary pneumococcal lung abscess in a five-year-old child is described. Secondary anaerobic infection as a cause of cavitation was excluded by bronchoscopic culture of the cavity. Streptococcus pneumoniae is a rare but recognized cause of lung abscess in healthy children.